Design and Comparison of Strategies for Level Control in a Nonlinear Tank - Urrea-Onate, E; Paez-Mejias, F (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
In this work, a study of the water level control of an inverted conical tank system is presented. This type of tank has highly nonlinear mathematical and dynamic characteristics. Four control strategies are designed, applied, and compared, namely classical Proportional–Integral– Derivative (PID), Gain Scheduling (GS), Internal Model Control (IMC), and Fuzzy Logic (FL). To determine which of the designed control strategies are the most suitable for an inverted conical tank, a comparative study of the behavior of the system is carried out. With this purpose, and considering situations much closer to reality, a variety of scenarios, such as step responses, random input disturbances, and momentary load disturbances, are conducted. Additionally, performance indexes (error-and statistics-based) are calculated to assess the system’s response. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.